2011
DOI: 10.1007/s00432-011-1034-9
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of lymph node metastasis and the suitability of 7th UICC N stage in predicting prognosis of remnant gastric cancer

Abstract: Preoperative diagnosis of depth of invasion and tumor size can help surgeons to evaluate LN metastasis. The 7th UICC N stage may be unsuitable and should be evaluated and improved in order to help surgeons rationally to estimate N stage of RGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 19 publications
1
22
1
Order By: Relevance
“…These observations raise the question about the suitability of the present TNM staging system to predict outcomes of GSC patients. Therefore, based on the results observed in our series, the N stage of 7th edition of TNM staging system seems unsuitable for GSC patients, which has also been claimed by Li et al [28]. …”
Section: Discussionsupporting
confidence: 66%
“…These observations raise the question about the suitability of the present TNM staging system to predict outcomes of GSC patients. Therefore, based on the results observed in our series, the N stage of 7th edition of TNM staging system seems unsuitable for GSC patients, which has also been claimed by Li et al [28]. …”
Section: Discussionsupporting
confidence: 66%
“…Our finding of a significantly smaller number of lymph nodes retrieved during CTG than during PTG is consistent with other studies showing that prior partial gastrectomy and lymphadenectomy results in retrieval of fewer perigastric lymph nodes on completion gastrectomy. 28,29 A greater proportion of lymph nodes are found to be positive in sporadic gastric cancer than in GRC, a difference that trended toward but did not reach significance in our sample. This may reflect different patterns of metastasis in GRC owing to altered lymphatic anatomy, which favours direct extension as a means of primary metastasis.…”
Section: Discussioncontrasting
confidence: 52%
“…The lymphatic flow and the pattern of LN spread of remnant gastric cancer are affected by the initial surgery and by the extent of adhesions between the remnant stomach and other organs, which in turn can increase the difficulty of the laparoscopic procedure. [21][22][23][24][25] After cutting the left gastric artery and its descending limb, the lymphatic drainage of the lesser curvature turns to the right side of the cardiovascular circuit and drains into the celiac artery. 21 Several workers have reported that lymphatic drainage of the greater curvature of the stomach drains into the splenic hilum and artery, and therefore metastasis is significantly more common in LNs no.…”
Section: Discussionmentioning
confidence: 99%